Acetylation-Dependent Regulation of Notch Signaling in Macrophages by SIRT1 Affects Sepsis Development - Bai, Xiaozhi; He, Ting; Liu, Yang; Zhang, Julei; Li, Xiaoqiang; Shi, Jihong; Wang, Kejia; Han, Fu; Zhang, Wei; Zhang, Yijie; Cai, Weixia; Hu, Dahai (Frontiers in Immunology, 2018)
SIRT1 is reported to participate in macrophage differentiation and affect sepsis, and Notch signaling is widely reported to influence inflammation and macrophage activation. However, the specific mechanisms through which SIRT1 regulates sepsis and the relationship between SIRT1 and Notch signaling remain poorly elucidated. In this study, we found that SIRT1 levels were decreased in sepsis both in vitro and in vivo, and that SIRT1 regulation of Notch signaling affected inflammation. In lipopolysaccharide (LPS)-induced sepsis, the levels of Notch signaling molecules, including Notch1, Notch2, Hes1, and NICD (Notch intracellular domain), were increased. However, NICD could be deacetylated by SIRT1, and this led to the suppression of Notch signaling. Notably, in macrophages from myeloid-specific RBP-J-/- mice, in which Notch signaling is inhibited, pro-inflammatory cytokines were expressed at lower levels than in macrophages from wild-type littermates, and in RBP-J-/- macrophages, the NF-κB pathway was also inhibited. Accordingly, in the case of RBP-J-/- mice, LPS-induced inflammation and mortality were lower than in wild-type mice. Our results indicate that SIRT1 inhibits Notch signaling through NICD deacetylation and thus ultimately alleviates sepsis.